Unsaturated polyester resin/polymethylmethacrylate waveguide-based refractive index sensor with dual-wavelength temperature compensation - Ian Yulianti, Ian Yulianti; Putut Marwoto, Putut Marwoto; Budi Astuti, Budi Astuti; Ngurah Made D P1 , Fianti, Ngurah Made D P1 , Fianti; Dhea Paradita, Dhea Paradita; Teguh Darsono, Teguh Darsono; Ngajikin, Nor Hafizah; Yaacob, Maslina; Cholan, Noran Azizan (iop, 2023)
This paper demonstrates an optical waveguide based- refractive index (RI) sensor using the temperature compensation method. The optical waveguide was formed using a polymethylmethacrylate sheet as the cladding material and unsaturated polyester resin as the core material. The sensor design consists of two input waveguide branches, a sensing area and an output branch. Two light emitting diodes with wavelength of 530 nm and 660 nm were used as light sources. In this work, temperature compensation was done by dual-wavelength technique in which RI and temperature sensitivities were measured at two different wavelengths at 530 nm and 660 nm. Based on the RI and temperature sensitivities, temperature compensation was implemented. Experimental fndings indicated that the average relative error of the uncompensated measurement using the light source of 530 nm and 660 nm were 0.4372% and 0.2749%, respectively. Meanwhile, the average error of the temperature compensation method was 0.0344%. Hence, the temperature compensation method provides measurement error up to 92% lower compared to the uncompensated method. As such, the proposed dual-wavelength compensation method could effectively improve the RI measurement accuracy.